Dietary patterns are influenced by socio-demographic conditions of women in childbearing age: a cohort study of pregnant women - Juliana Araujo Teixeira; Teresa Gontijo Castro; Cameron C. Grant; Clare R. Wall; Ana Lúcia da Silva Castro; Rossana Pulcineli Vieira Francisco; Sandra Elisabete Vieira; Silvia Regina Dias Medici Saldiva; Dirce Maria Marchioni (BMC, 2018)
Abstract Background Women's health during their reproductive years and whilst pregnant has implications for their children's health, both in utero and during childhood. Associations of women's pre-pregnancy dietary patterns (DP) with maternal socio-demographic characteristics and nutrient intake were investigated in ProcriAr cohort study in São Paulo/Brazil, 2012. Methods The DPs of 454 women were investigated by principal component factor analysis, using dietary information from a validated 110-item food frequency questionnaire. Multiple linear regression models identified independent associations between DPs and maternal socio-demographic characteristics and Spearman's correlation determined associations between DPs and nutrients intake. Results Participants' mean age was 26.1 years (standard deviation = 6.3), 10.3% had more than 8 years of formal education, 30% were migrants from outside of the Southeast of Brazil, 48% were employed, 13% were smokers, and 51% were overweight/obese. Four DPs were derived: 'Lentils, whole grains and soups,' 'Snacks, sandwiches, sweets and soft drinks,' 'Seasoned vegetables and lean meats,' and 'Sweetened juices, bread and butter, rice and beans'. The 'Lentils, whole grains and soups' score was positively related to maternal age, being non-smoker and born in the South, North or Midwest of Brazil. The 'Snacks, sandwiches, sweets and soft drinks' score was positively related to higher maternal education, and negatively related to age, lack of formal work and being born in the Northeast region. The 'Seasoned vegetables and lean meats' score was positively related to higher maternal education. The 'Sweetened juices, bread and butter, rice and beans' score was positively related to unemployment and to no family history of hypertension, and negatively related to maternal overweight and obesity. Dietary intake of fruits and vegetables, foods that require preparation, nutrients from one-carbon metabolism, protein, iron, calcium and vitamin D were correlated with the 'Seasoned vegetables and lean meats'. Dietary intake of sugar-sweetened and alcoholic beverages, industrialized and takeaway foods, and foods rich in sugar, energy, fat, and synthetic folate were correlated with the 'Snacks, sandwiches, sweets and soft drinks'. Conclusions Findings from this study add perspectives to be considered in the implementation of health interventions, which could improve women's nutritional status and provide an adequate environment for the developing fetus.